PENGARUH WORD OF MOUTH (WOM) DAN KELENGKAPAN PRODUK TERHADAP KEPUTUSAN PEMEBLIAN PADA MINIMARKET SINAR BULAN - Sadiqin, Amin; Perdana, Buyung Cahya; Arvita, Rizki; Hariono, Jefri (PUTRA JAWA PUBLISHER, 2024)
The aim of this study is to determine and analyze the influence of word of mouth and product diversity variables on purchasing decisions at Sinar Bulan minimarket. The research population consists of Sinar Bulan minimarket consumers. A sample of 100 people was taken using random sampling techniques. The research results prove that both word of mouth and product diversity have a positive and significant partial effect on purchasing decisions at Sinar Bulan minimarket. Furthermore, word of mouth and product diversity simultaneously have a positive and significant effect on purchasing decisions at Sinar Bulan minimarket. The magnitude of the influence of word of mouth and product diversity on purchasing decisions at Sinar Bulan minimarket is 44.8%.